Online Collaborative Learning in Higher Education in Albania: Some Necessary Innovations - Eriola Qafzezi (International School for Social and Business Studies, 2023)
Purpose: The purpose of the current paper is to discuss the necessity for the internationalisation of Albanian HEIs, in light of the recent changes that HEIs in Albania are undergoing. Online collaborative learning is thus introduced as a necessary innovation to be embraced in HE in Albania, illustrated by implementation and findings and comments based on an authentic case study undertaken in the third course, Bachelor level, Fan S. Noli University, Korça, Albania.  Study design/methodology/approach: The paper is supported by a theoretical background on online collaborative learning and factual data about the current state of HEIs in Albania. The latter factual information illustrates the necessity of embracing online learning practices through collaborative learning, supported by examples from the case study. The paper adopts a mixed method approach, combining qualitative analysis with quantitative data derived from surveys carried out with Albanian students. Findings: There are some conclusions and findings that we have derived from the factual information presented about the current state of HEIs in Albania, combined with data extracted from the case study. They point to the necessary innovations involving Albanian teachers and students of HEIs in online collaborative learning.   Originality/value: The current study bears original value because it provides direct links between the current need for the internationalisation of HEIs in Albania and online collaborative learning as a concrete way to bring about internationalisation. Examples brought are also authentic, taken from the case study, supported by data from pre- and post-implementation surveys conducted with Albanian students who took part in the case study.